Challenging private law : Lord Sumption on the Supreme Court - Worthington, Sarah; Day, William (Editor of challenging private law) (London [England] : Hart Publishing, 2020)
"Lord Sumption has been one of the most influential judges of his generation. This book critically reflects on the important and controversial issues posed by his jurisprudence. Using Lord Sumption's contributions as a springboard, the book contains a selection of essays that consider 'where next' in relation to topics such as: - contractual interpretation; - tortious duties of care; - compensatory damages; - proprietary restitution; - piercing the corporate veil. The book covers a broad range of areas in private law including contract, tort, unjust enrichments, equity, company and commercial law, as well as private international law and civil procedure"--
Introduction / Lord Sumption -- Interpretation / Ewan McKendrick -- Variation and Waiver / William Day -- Termination / Sir David Foxton -- Contract Damages / Adam Kramer -- Penalties / Edwin Peel -- The Contract/Tort Borderline / Janet O'Sullivan -- Personal Injury / Nicholas J McBride -- Injunctions / Donal Nolan -- Unjust Enrichment / Graham Virgo -- Proprietary Restitution / William Day and Sarah Worthington -- Knowing Receipt / Jamie Glister -- Illegality / Charlie Webb -- Agency / Peter Watts -- Attribution / Ernest Lim -- Powers / Sarah Worthington -- Piercing the Corporate Veil / Christian Witting -- Good Arguable Case / Joshua Folkard and Ian Bergson -- Forum Conveniens / Louise Merrett -- Foreign Law / Richard Fentiman -- Res Judicata / The Hon KR Handley QC -- Privilege / Bankim Thanki QC, Chloe Carpenter QC, Nik Yeo and Rebecca Loveridge.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Sumption, Jonathan; Great Britain. -- Supreme Court; Great Britain. -- Supreme Court -- Officials and employees; Civil law -- England; Conflict of laws -- England; Judicial opinions -- England; Private / Civil law: general works; Electronic books